Impact of a Shared Decision Making Intervention on Health Care Utilization: A Secondary Analysis of the Chest Pain Choice Multicenter Randomized Trial. (26th December 2017) - Schaffer, Jason T.; Hess, Erik P.; Hollander, Judd E.; Kline, Jeffrey A.; Torres, Carlos A.; Diercks, Deborah B.; Jones, Russell; Owen, Kelly P.; Meisel, Zachary F.; Demers, Michel; Leblanc, Annie; Inselman, Jonathan; et al.
Abstract: Background: Patients at low risk for acute coronary syndrome are frequently admitted for observation and cardiac testing, resulting in substantial burden and cost to the patient and the health care system. Objectives: The purpose of this investigation was to measure the effect of the Chest Pain Choice (CPC) decision aid on overall health care utilization as well as utilization of specific services both during the index emergency department (ED) visit and in the subsequent 45 days. Methods: This was a planned secondary analysis of data from a pragmatic multicenter randomized trial of shared decision making in adults presenting to the ED with chest pain who were being considered for observation unit admission for cardiac stress testing or coronary computed tomography angiography. The trial compared an intervention group engaged in shared decision making facilitated by the CPC decision aid to a control group receiving usual care. Hospital‐level billing data were used to measure utilization for the index ED visit and during the following 45 days. Patients in both groups also were asked to keep a diary recording health care utilization over the same 45‐day period. Outcomes assessed included length of time in the ED and observation, ED visits, office visits, hospitalizations, testing, imaging, and procedures. Results: Of the 898 patients included in the original trial, we were able to contact 834 (92.9%) patients for 45‐day health care diary review. There was no difference in patient‐reported health care utilization between the study arms. Hospital‐level billing data were obtained for all 898 (100%) patients. During the initial ED visit the length of stay (LOS) was similar, and there was no difference in the frequency of observation unit admission between study arms. However, the mean observation unit LOS was 95 minutes (95% confidence interval [CI] = 40.8–149.8) shorter in the CPC arm and the mean number of tests was lower in the CPC arm (decrease in 19.4 imaging studies per 100 patients, 95% CI = 15.5–23.3). When evaluating the entire encounter and follow‐up period, the intervention arm underwent fewer tests (decrease in 125.6 tests per 100 patients, 95% CI = 29.3–221.6). More specifically, there were fewer advanced cardiac imaging tests completed (25.8 fewer per 100 patients, 95% CI = 3.74–47.9) in the intervention arm. Conclusions: Shared decision making in low‐risk chest pain can lead to decreased diagnostic testing without worsening outcomes measured over 45 days.